Aplicação dos conceitos de “confusão patrimonial” e “desvio de finalidade” após as alterações trazidas pela Lei de Liberdade Econômica (Lei nº 13.874/2019) - Naufal, Fernanda Pasinato (2023)
The Law No. 13.874/2019 included among its themes the amendment of article 50 of the Civil Code regarding the application of disregard of corporate entity, within the scope of business law. Regarding the normative device, the new law aimed to bring more objective criteria about the elements that characterize the abuse of the legal entity, i.e., the concepts of commingling of assets and the misuse of purpose. Thus, this work intends to analyze whether, after the legislative change, there was any change in the understanding of the Judiciary about the application of the disregard doctrine and the concepts mentioned above, in order to remove the criticism that had been identified by the legal community, especially with regard to the indiscriminate application of the disregard doctrine in the Brazilian legal system